The Leopard and the Sky God - Retold by Mackinnon, Mairi (London Usborne Publishing Ltd, 2007)
In this lovely African tale, set long, long ago, the leopard has a spendid new drum - and the Sky God wants it. Along the way, the tortoise gets a shell and thunder is made for the very first time"--Back cover.
Keywords: Fables, African -- Leopard